Detecting second mesiobuccal canal in maxillary first molars in Erbil citizens: CBCT Retrospective study. - Mustafa T. Mohamadamin; Karam A. Thiab; Ribwar F. Khalid; Khidir M. Khidir (Erbil Dental Journal)
Background and Objectives: The success of root canal therapy is depending on cleaning and shaping of the root canals. The root canals have complex morphology and wide individual variations. The purpose of this study was to investigate the prevalence of second mesiobuccal canal (MB2) of maxillary first molars in Erbil population using cone-beam computed tomography (CBCT). Materials and Methods: A total of 101 permanent maxillary first molars were randomly se-lected from Erbil citizens. All teeth were examined for the number of root canals and the presence of second mesiobuccal canal by Cone Beam Computed Tomography (CBCT). Result: The MB2 canal was found in 80.2% (the 95% CI is 72.3% to 87.1%) of the analyzed cases (81/101). Conclusion: The second mesiobuccal canal was found in a high percentage of the samples. And it is within normal magnitude in comparison with the common findings in the literature. These results indicate that CBCT is an effective, high-precision diagnostic tool for detecting canals.